Evaluating components of dental care utilization among adults with diabetes and matched controls via hurdle models - Chaudhari Monica; Hubbard Rebecca; Reid Robert J; Inge Ronald; Newton Katherine M; Spangler Leslie; Barlow William E (BMC, 2012)
Abstract Background About one-third of adults with diabetes have severe oral complications. However, limited previous research has investigated dental care utilization associated with diabetes. This project had two purposes: to develop a methodology to estimate dental care utilization using claims data and to use this methodology to compare utilization of dental care between adults with and without diabetes. Methods Data included secondary enrollment and demographic data from Washington Dental Service (WDS) and Group Health Cooperative (GH), clinical data from GH, and dental-utilization data from WDS claims during 2002-2006. Dental and medical records from WDS and GH were linked for enrolees continuously and dually insured during the study. We employed hurdle models in a quasi-experimental setting to assess differences between adults with and without diabetes in 5-year cumulative utilization of dental services. Propensity score matching adjusted for differences in baseline covariates between the two groups. Results We found that adults with diabetes had lower odds of visiting a dentist (OR = 0.74, p < 0.001). Among those with a dental visit, diabetes patients had lower odds of receiving prophylaxes (OR = 0.77), fillings (OR = 0.80) and crowns (OR = 0.84) (p < 0.005 for all) and higher odds of receiving periodontal maintenance (OR = 1.24), non-surgical periodontal procedures (OR = 1.30), extractions (OR = 1.38) and removable prosthetics (OR = 1.36) (p < 0.001 for all). Conclusions Patients with diabetes are less likely to use dental services. Those who do are less likely to use preventive care and more likely to receive periodontal care and tooth-extractions. Future research should address the possible effectiveness of additional prevention in reducing subsequent severe oral disease in patients with diabetes.